SUPERVISI DALAM PELATIHAN - Inda Fitriani Effendi (Jurnal Manajemen Pendidikan, 2014)
this research aims to understand about: (1) training process. training based on supervision is one way to monitor teaching improvement as well as the teachers. The process of training start from planning, analyse, assessment, training and development, program content, learning principle, actual program, skill knowledge ability of works, evaluation (2) process supervision trough several steps and the process itself base on colabbotarive , creative and supportive supervision (3) supervision not only held by school but also the trainer from another institution are requested to do supervision in classrooms in order to monitor the learning process. The supervision will be held at the end of training session. (4) Empowering is one way to help teacher to be improved in order to do efective work. Empowering also means to recoqnize the teachers’ right and obligation. Teacher who is able to achieve Teaching Knowledge Test, will be put as a teacher model that can help other teachers to be improved.